Structure of O-Polysaccharide and Lipid A of Pantoea Agglomerans 8488 - Tetiana V. Bulyhina; Evelina L. Zdorovenko; Ludmila D. Varbanets; Alexander S. Shashkov; Alexandra A. Kadykova; Yuriy A. Knirel; Oleh V. Lushchak (Biomolecules, 2020)
The Pantoea agglomerans 8488 lipopolysaccharide (LPS) was isolated, purified and characterized by monosaccharide and fatty acid analysis. The O-polysaccharide and lipid A components of the LPS were separated by mild acid degradation. Lipid A was studied by electrospray ionization mass spectrometry (ESI-MS) and found to consist of hexa-, penta-, tetra- and tri-acylated species. Two-dimensional nuclear magnetic resonance (NMR) spectroscopy revealed the following structure of the O-polysaccharide repeating unit →3)-α-L-Rhap-(1→6)-α-D-Manp-(1→3)-α-L-Fucp-(1→3)-β-D-GlcNAcp-(1→. The LPS showed a low level of toxicity, was not pyrogenic, and reduced the adhesiveness index of microorganisms to 2.12, which was twofold less than the control. LPS modified by complex compounds of germanium (IV) and tin (IV) were obtained. It was found that six LPS samples modified by Sn compounds and two LPS samples modified by Ge compounds lost their toxic activity when administered to mice in a dose of LD50 (105 µg/mice or 5 mg/kg). However, none of the modified LPS samples changed their serological activity in an Ouchterlony double immunodiffusion test in agar.